Pengaruh Likuiditas, Leverage, dan Margin Laba Bersih terhadap Pemilihan Metode Penilaian Persediaan pada Perusahaan Dagang yang Terdaftar di BEI Tahun 2018-2020 - Nariani, Pande Putu Ayu Suci; Julianto, I Putu (Universitas Pendidikan Ganesha, 2021)
Abstract This study aims to prove and analyze the effect of liquidity, leverage, and net profit margin on the selection of inventory valuation methods in trading companies listed on the Indonesia Stock Exchange in 2018-2020. Using a quantitative approach method with secondary data and data analysis techniques, namely logistic regression analysis, the analysis used to measure how far the influence of the independent variable on the dependent variable in the form of a dummy variable. The population of this study is a trading company, both wholesale and retail, with the determination of the sample using purposive sampling technique. A sample of 27 companies was obtained to be studied for three periods with the calculation using SPSS version 25 with accurate explanation results. The technique of collecting data through the official website of the Indonesia Stock Exchange is the annual financial report of each registered trading company during the observation period. The research shows that Liquidity, Leverage, and Net Profit Margin have a positive influence either partially or simultaneously on the selection of inventory valuation methods with a research accuracy rate of 41.8%. Keywords: Liquidity, Leverage, Net Profit Margin, and Inventory Valuation Method